Effectiveness of specific RNA-mediated interference through ingested double-stranded RNA in Caenorhabditis elegans - Kamath, Ravi S (BioMed Central, 2001)
BACKGROUND: In Caenorhabditis elegans, injection of double-stranded RNA (dsRNA) results in the specific inactivation of genes containing homologous sequences, a technique termed RNA-mediated interference (RNAi). It has previously been shown that RNAi can also be achieved by feeding worms Escherichia coli expressing dsRNA corresponding to a specific gene; this mode of dsRNA introduction is conventionally considered to be less efficient than direct injection, however, and has therefore seen limited use, even though it is considerably less labor-intensive. RESULTS: Here we present an optimized feeding method that results in phenotypes at least as strong as those produced by direct injection of dsRNA for embryonic lethal genes, and stronger for genes with post-embryonic phenotypes. In addition, the interference effect generated by feeding can be titrated to uncover a series of hypomorphic phenotypes informative about the functions of a given gene. Using this method, we screened 86 random genes on consecutive cosmids and identified functions for 13 new genes. These included two genes producing an uncoordinated phenotype (a previously uncharacterized POU homeodomain gene, ceh-6, and a gene encoding a MADS-box protein) and one gene encoding a novel protein that results in a high-incidence-of-males phenotype. CONCLUSIONS: RNAi by feeding can provide significant information about the functions of an individual gene beyond that provided by injection. Moreover, it can be used for special applications for which injection or the use of mutants is sometimes impracticable (for example, titration, biochemistry and large-scale screening). Thus, RNAi by feeding should make possible new experimental approaches for the use of genomic sequence information.